SPILANTHES ACMELLA AND PHYSICAL EXERCISE INCREASED TESTOSTERONE LEVELS AND OSTEOBLAST CELLS IN GLUCOCORTICOID-INDUCED OSTEOPOROSIS MALE MICE - Laswati, Hening; Subadi, Imam; Widyowati, Retno; Agil, Mangestuti; Pangkahila, Jahya Alex (BALI MEDICAL JOURNAL, 2015)
Background: Glucocorticoid-induced osteoporosis is leading cause of secondary osteoporosis by decreasing formation activity and increasing resorption activity. Spilanthes acmella, is one of Indonesia medicinal plants that contain of polyphenol and flavonoids. Previously in vitro study showed that buthanol and water fraction from this plant have increased alkaline phosphatase that known as marker of bone formation. The objective of this study to analyze the effect of Spilanthes acmella and physical exercise in increasing testosterone and osteoblast cells of femoral’s trabecular glucocorticoid-induced osteoporosis male mice. Method: This study using a posttest control group design, 36 male healthy mice (5 months old) were randomizely devided into 6 groups, there are : 1.Healthy control group (without induction dexamethaxone), 2.Osteoporosis groups (induction with dexamethaxone without treatment), 3.Positive control receive suspension alendronat, 4.70% Ethanol extract of Spilanthes acmella group, 5.Combination group of 70% extract ethanol of Spilanthes acmella and exercise, and 6.Exercise group (walking using mice treadmill 10m/minute, 5-12 minutes 3 times a week). All of the intervention were given for 4 weeks. The serum levels of testosterone were determined using immunoserology (ELISA) and osteoblast cells were determined histomorphometry by light microscopy. All statistical test were carried out using SPSS 23 and statistical significance was set at p 0.05). Conclusion: It proved that 70% ethanol extract of Spilanthes acmella have an additive effect to weight bearing exercise in glucocorticoid-induced osteoporosis male mice.
Keywords: Glucocorticoid; Induced; Osteoporosis; Spilanthes acmella; Testosterone